Hubungan Pemberian Terapi Oksigen Hiperbarik Terhadap Aktifitas Osteoblastik Dan Osteoklastik Pada Tikus Model Fraktur - CALVIN JUSO HANDONO; TOTOT MUDJIONO; ANNISA ULLYA RASYIDA (HANG TUAH MEDICAL JOURNAL, 2022)
Background : Fracture is a condition where the bone is cut off due to significant pressure which can be in the form of bending, twisting, or pulling due to trauma, work accidents, traffic accidents, as well as degeneration and pathological processes. Fractures can result in loss of productivity and individual disability. One of the adjuvant therapies to accelerate the bone healing process in patients with fractures is hyperbaric oxygen (HBO) therapy. Objective: The purpose of this study was to determine the effect of Hyperbaric Oxygen therapy on the amount of osteoblasts and osteoclasts formed in ratsmodeled with diaphyseal femur fractures. Methods: This research is an experimental study using a post test only control group design. The object of this study is a rat fracture model with TOHB therapy as the independent variable and a fracture model without HBO therapy as a control variable. Results: The results of this study showed positive results on the effect of HBO therapy on the formation of osteoblastic and osteoclastic cells. Conclusion: There was a significant difference in the number of osteoblast and osteoclast in fracture model mice treated with HBO compared to those not treated with HBO. Keywords: HBO therapy, Fracture, Callus, Osteoblast, Osteoclast, Wistar Rat